2022
DOI: 10.2147/ndt.s386179
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Negative Life Events and Nonsuicidal Self-Injury Among Chinese Adolescents: A Moderated-Mediation Model

Abstract: Objective This study aimed to investigate whether anxiety mediates the relationship between negative life events and nonsuicidal self-injury (NSSI) in adolescents and whether this mediating role is moderated through social support. Methods The model consisted of an anonymous questionnaire survey of 506 Chinese adolescents (253 boys and 253 girls, mean age 15.11 years (SD = 1.83, range 11–18 years)). Self-designed questionnaires were used to collect demographic data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
1
Order By: Relevance
“…This is in line with previous studies that have also found a strong relationship between stressful life events and NSSI. 12 , 55 However, our results diverge from a handful of studies that did not find a significant direct effect. 56 One possible explanation for this discrepancy could be the different demographic backgrounds of the study samples.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in line with previous studies that have also found a strong relationship between stressful life events and NSSI. 12 , 55 However, our results diverge from a handful of studies that did not find a significant direct effect. 56 One possible explanation for this discrepancy could be the different demographic backgrounds of the study samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings also provide a new perspective for preventing NSSI among college students [ 37 ]. Therefore, we developed and evaluated a moderation model to clarify the role of multilevel factors, including NLEs, MH, and sex, on NSSI [ 16 ]. A more comprehensive understanding of NSSI and its associated factors may be helpful in developing programs and interventions to reduce the occurrence of NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies have established that NLEs and MH are associated with higher NSSI [ 14 , 17 ], and we observed an association between the two in our study. Our analysis is based on the hypothesis of psychopathological development resulting from the interplay between NLEs and behavioral and MH issues [ 16 ]. These findings offer a theoretical foundation for a comprehensive investigation of its role in understanding the relationships between NLEs, MH, and NSSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations